Pengaruh Profitabilitas, Growth Opportunity, dan Umur Perusahaan Terhadap Nilai Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2018-2022 - Anjeli Aja; Melisa Jumatun Ulya; M. Redo Akbar; Mashabi Mashabi; Titin Agustin Nengsih (Jurnal Akuntansi dan Pajak, 2024)
This study aims to test and analyse the effect of profitability, growth opportunity, and company age on firm value in food and beverage subsector manufacturing companies listed on the IDX in 2018-2022. The sampling method used in this study was purposive sampling technique and obtained a sample of 10 companies. The data analysis method used in this study is panel data regression analysis. The results showed that profitability has a significant positive effect on firm value, while growth opportunity and company age have no effect on firm value.